2017
DOI: 10.1371/journal.pone.0170984
|View full text |Cite
|
Sign up to set email alerts
|

Ilexsaponin A attenuates ischemia-reperfusion-induced myocardial injury through anti-apoptotic pathway

Abstract: The protective effects of ilexsaponin A on ischemia-reperfusion-induced myocardial injury were investigated. Myocardial ischemia/reperfusion model was established in male Sprague–Dawley rats. Myocardial injury was evaluated by TTC staining and myocardial marker enzyme leakage. The in vitro protective potential of Ilexsaponin A was assessed on hypoxia/reoxygenation cellular model in neonatal rat cardiomyocytes. Cellular viability and apoptosis were evaluated by MTT and TUNEL assay. Caspase-3, cleaved caspase-3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Therefore, oxidative stress burden has been implicated in the development of isoproterenol-induced changes in mitochondria, alterating the enzyme activity and transport systems and causing disturbances in cellular homeostasis. 60 -62 The present results agree with some published data that highlight the critical link between HFD/isoproterenol-induced cardiotoxicity and the development of oxidative stress burden as evidenced by the ROS generation and depression in the endogenous antioxidant system. 3,4,59 Additionally, and in harmony with other studies 17,22,23,43,63 the ischemic ameliorating effect of levosimendan and to a lesser extent cilostazol on increments in the inflammatory markers was evident.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, oxidative stress burden has been implicated in the development of isoproterenol-induced changes in mitochondria, alterating the enzyme activity and transport systems and causing disturbances in cellular homeostasis. 60 -62 The present results agree with some published data that highlight the critical link between HFD/isoproterenol-induced cardiotoxicity and the development of oxidative stress burden as evidenced by the ROS generation and depression in the endogenous antioxidant system. 3,4,59 Additionally, and in harmony with other studies 17,22,23,43,63 the ischemic ameliorating effect of levosimendan and to a lesser extent cilostazol on increments in the inflammatory markers was evident.…”
Section: Discussionsupporting
confidence: 91%
“…Previous findings have suggested that gypenoside protects the cardiomyocytes against the injury via the mitogen-activated protein kinase-mediated nuclear factor-κB pathway (26). In addition, as the convergent pathway of final ischemia and reperfusion injury, mitochondria-mediated apoptosis has been demonstrated to be involved in protective effects of most phytochemicals, including clematichinenoside (27) and ilexsaponin A (28).…”
Section: Discussionmentioning
confidence: 99%
“…The unstained myocardium was incubated for 30 min at 37°C in TTC (1% in 0.1 mol/L phosphate buffer, pH 7.4). The non-infarcted myocardium was deep red, in contrast to the pale of the infarcted myocardium (Zhang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%